PENINGKATAN KOMPETENSI PEDAGOGIK GURU DALAM MEMBUAT ALAT PERAGA PEMBELAJARAN MELALUI WORKSHOP KKG SEKOLAH DI SD PANGGANG - Parjiyatmi Parjiyatmi (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2019)
This study aim to improve the teacher paedagogic competence in making learning instrument through the workshop of teacher task-force group at SD Panggang, Bambanglipuro, Bantul, at academic year of 2017/2018. This study was conducted in two cycles. Subject of the study were class teachers and subject teachers at SD Panggang, Bambanglipuro, Bantul. The study consisted a series steps, i.e. planning, action, observation, and reflection. Data collected by using observation technique and giving an assignment in the workshop. The data then analyzed by using comparative descriptive technique. Result of the study showed there were 30.36% academic supervision finding in the workshop of teacher task-force group in SD Panggang, Bambanglipuro, Bantul, at academic year of 2017/2018.